PENGEMBANGAN SOAL-SOAL OPEN-ENDED PADA POKOK BAHASAN SEGITIGA DAN SEGIEMPAT DI SMP - Yusuf, Mariska; Zulkardi; Saleh, Trimurti (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2009)
The research is proposed to: (1) get open-ended problems which are valid and practice on the math topic Triangle and Rectangle in junior high school. (2) find potential effects of open ended problems to the students on the topic about triangle and rectangle in junior high school. The methodology that use in this study is a developmental research. Subject of this research is 35 students of seventh grade (VII.10) at SMP Negeri 2 Banyuasin III. The way of collecting data is by using interview, document analysis, and test of open ended problems. All data have been collected was analysed by using qualitative descriptive. The result of data analysis come to conclusion, that: (1) This research produces open ended problems on the topic of triangle and rectangle for students of VII grade are valid and practice. The validity was described by the result of validator scores, where the all validators state that the instrument have been valid based on content, construction and language. The validity was also described by the validation the problems in small group. The practical was described by testing the problem to a small group where most of the students were able to solve the open-ended problems given. (2) The prototype of open-ended problems which was developed have positive potential effect to the result of student learning process, and it is shown by the variety of the students’ answers and the average of complete students of 3 time tests of open-ended problems which resulted 77,2%. DOI: 10.22342/jpm.3.2.327